Facial visible spectrophotometric determination of metformin hydrochloride in glucosam tablets and industrial waste water: Application to content uniformity testing - Nief Rahman Ahmad (University of Mosul, 2012)
Objectives: To determine simple, accurate and highly sensitive spectrophotometric method for determination metformin hydrochloride in pharmaceutical preparations and in industrial waste water sample. Materials and Method: The method is based on the oxidation of metformin by a known excess of sodium hypochlorite in alkaline medium. Results: Formation of a yellow-colored chromophore having maximum absorbance at 385nm. Molar absorptivity was found to be 2 × 104 L.mol-1.cm-1. Beer's law is obeyed in the concentration range of 0.5-4 µg .ml-1, relative standard deviation (RSD) is better than ±1.8 (n =10) .The limits of detection and quantitation are 0.083 and 0.25 µg .mL-1, respectively. The method is applied successfully to determination of metformin pharmaceutical formulation (tablets).The common excipients do not interfere with the proposed method. A statistical comparison of these results with those of official method using t and F values at 95% confidence level shows good agreements and indicated no significant difference in the precision, and the present method has good validity. Conclusion: The proposed method can be used as a routine quality control and content uniformity tests for determination of metformin in pure form, tablet formulations and industrial waste water sample.